2022
DOI: 10.3389/fped.2022.815857
|View full text |Cite
|
Sign up to set email alerts
|

Protective SARS-CoV-2 Antibody Response in Children With Inflammatory Bowel Disease

Abstract: BackgroundTo date, there's no evidence of an increased risk of SARS-CoV-2 infection or more severe COVID-19 in patients with inflammatory bowel disease (IBD). However, whether COVID-19 alters the clinical course of IBD or whether IBD treatment affects the immunological response to SARS-CoV-2 is still under investigation, especially in children.AimTo assess the serological response to SARS-CoV-2 in children with IBD, and to evaluate the impact of COVID-19 on the clinical course of IBD.Material and MethodsThis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…A lower severity of COVID-19 has been shown also by other authors (24,33,34). Allocca et al found that the case fatality rate was 0% in IBD patients and 13%-15% in the general population (24) (35). Four remained asymptomatic and 8 had only mild clinical manifestations.…”
Section: Clinical Course and Severity Of Covid-19 In Patients With In...mentioning
confidence: 62%
See 4 more Smart Citations
“…A lower severity of COVID-19 has been shown also by other authors (24,33,34). Allocca et al found that the case fatality rate was 0% in IBD patients and 13%-15% in the general population (24) (35). Four remained asymptomatic and 8 had only mild clinical manifestations.…”
Section: Clinical Course and Severity Of Covid-19 In Patients With In...mentioning
confidence: 62%
“…A more recent study by Bosa et al. including 12 children aged 12-18 years (9 CD, 1 UC and 2 IBDU) among whom 11 were receiving immunosuppressive therapy revealed that the antibody response to SARS-CoV-2 infection was quite similar to that detected in 48 healthy children convalescent after COVID-19, matched for sex, age, time of SARS-CoV-2 infection and COVID-19 severity (27.3 ± 43.8 kAU/L vs 36.8 ± 35.3 kAU/L; p=0.451) ( 35 ). On the contrary, Dailey et al.…”
Section: Immune Response Of Patients With Inflammatory Bowel Disease ...mentioning
confidence: 70%
See 3 more Smart Citations